2007
DOI: 10.1577/m06-115.1
|View full text |Cite
|
Sign up to set email alerts
|

Electrofishing Effort Required to Estimate Biotic Condition in Southern Idaho Rivers

Abstract: An important issue surrounding biomonitoring in large rivers is the minimum sampling effort required to collect an adequate number of fish for accurate and precise determinations of biotic condition. During the summer of 2002, we sampled 15 randomly selected large‐river sites in southern Idaho to evaluate the effects of sampling effort on an index of biotic integrity (IBI). Boat electrofishing was used to collect sample populations of fish in river reaches representing 40 and 100 times the mean channel width (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…Site-scale sampling design includes specifying the spatial scale over which the sample(s) will be collected (site length), the amount and types of habitats that will be sampled within that site, the field sampling methods to be used, the estimated number of person-hours (Reynolds et al, 2003;Flotemersch et al, 2006a;Hughes and Peck, 2008), and, sometimes, a minimum number of fish to be caught (Dußling et al, 2004;Hughes and Herlihy, 2007;Maret et al, 2007;USEPA, 2007).…”
Section: Sampling Site Lengthmentioning
confidence: 99%
See 3 more Smart Citations
“…Site-scale sampling design includes specifying the spatial scale over which the sample(s) will be collected (site length), the amount and types of habitats that will be sampled within that site, the field sampling methods to be used, the estimated number of person-hours (Reynolds et al, 2003;Flotemersch et al, 2006a;Hughes and Peck, 2008), and, sometimes, a minimum number of fish to be caught (Dußling et al, 2004;Hughes and Herlihy, 2007;Maret et al, 2007;USEPA, 2007).…”
Section: Sampling Site Lengthmentioning
confidence: 99%
“…With exceptions (e.g. Lyons et al, 2001;Cao et al, 2001;Hughes et al, 2002;Reynolds et al, 2003 and references cited therein;Flotemersch and Blocksom, 2005;Hughes and Herlihy, 2007;Maret et al, 2007;LaVigne et al, 2008aLaVigne et al, , 2008b, site length designations have been based on judgment, tradition, untested assumptions or the need to match some other aspect of sampling or management activities. The purpose of this paper is not intended to be an exhaustive review of the topic; rather, it is to provide an overview of different approaches that have been used for site length determination, and to help provide a technical foundation for improving future studies of sampling effort.…”
Section: Approaches For Determining Sampling Site Lengthmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, smaller sample sizes are sufficient to estimate diversity using diversity or biotic indices (Lloyd et al, 1968;Magurran, 2004). For instance, Hughes and Herlihy (2007) and Maret et al (2007) found that the estimation of adequate scores for indices of biotic integrity (IBI) required less sampling effort than estimates of fish species richness.…”
Section: Introductionmentioning
confidence: 99%